Use of negative pressure wound therapy with instillation to salvage infected implants: a retrospective review of cases - Rebecca McLean; Meredith Simcock; Alessandra Canal; Michelle Locke (Australasian Journal of Plastic Surgery)
**Introduction:** Periprosthetic breast implant infections are a well-known but devastating complication of breast reconstruction, occurring in up to 35 per cent of patients postoperatively. Historically, surgical washout and explantation was common practice to control infection, often sacrificing the reconstruction. **Methods:** After successfully using negative-pressure wound therapy with instillation (Veraflo, Intermed, Auckland) on lower leg wounds, we transferred the use of this technology to infected breast pockets. **Results:** In the first year using negative-pressure wound therapy with instillation, our department managed seven patients (eight breast reconstructions) presenting with breast device infection at an average of 15.3 days postoperatively. The average length of stay for treatment was 7.4 days with 2.5 operations over this period. Four patients had attempted salvage of their reconstructive pocket and all were discharged with a breast expander in situ. **Conclusion:** Attempted salvage using negative-pressure wound therapy with instillation may improve rates of reconstruction salvage after periprosthetic infection. We present our current management algorithm for periprosthetic infections.